Manajemen risiko pada akad pembiayaan murabahah dalam praktik perbankan syariah: Studi literatur - Alisa, Siti Nur (Maliki Interdisciplinary Journal, 2026)
This study aims to explore risk management in murabahah financing contracts within the Islamic banking environment using a literature review. Murabahah financing products dominate Islamic bank portfolios due to their structural simplicity and relatively lower risk levels compared to other alternative contracts. However, these financing activities remain exposed to a number of significant risks, such as credit risk, operational risk, liquidity risk, and Sharia compliance risk. This research approach is based on a literature review involving an in-depth analysis of various scientific journals, books, and related published documents. The main findings reveal that risk management in murabahah financing is implemented through a series of processes, including evaluating the debtor's eligibility, determining collateral, ongoing financing supervision, and implementing prudential principles and Sharia compliance. Furthermore, the effectiveness of risk management depends on the synergy between the technical elements of conventional banking and Islamic values. This study is anticipated to enrich risk management practices in murabahah financing, thereby supporting the improvement of the financial stability and performance of the Islamic banking sector.